A targeted approach for multiplex detection of respiratory viruses in cases with severe acute respiratory infections by nanopore sequencing - Arghavan Zebardast; Kaveh Sadeghi; Ahmad Nejati; Sevrin Zadheidar; Mohammad Hossein Najmi; Adel Abedi; Vahid Salimi; Mehdi Shabani; Jila Yavarian; Nazanin Zahra Shafiei Jandaghi; Talat Mokhtari Azad (PLoS ONE, 2025)
Severe acute respiratory infection (SARI) remains one of the leading causes of morbidity and mortality worldwide. Multiple viruses can cause this infection. Sequencing technologies hold great promise for detecting viral pathogens. This proof-of-concept study aimed to develop and validate a new method for multiplex detection and typing of SARI-related viruses (SARS-CoV-2, Influenza A (H1N1, H3N2), Influenza B, human respiratory syncytial virus, human adenoviruses, human enteroviruses, and human parainfluenza viruses) using a nanopore next-generation sequencing method. Following genome extraction from oropharyngeal swab samples and conventional RT-PCR assays, the libraries were barcoded and sequenced by the MinION device. The sensitivity and specificity were assessed using various serial dilutions of samples and different primer pools, respectively. Data analysis was carried out using bioinformatic tools. Finally, the protocol was validated with known positive samples. All participants provided written informed consent. During 12 hours of MinION sequencing, 711,000 reads passed the quality filters (Q-score>7). Eleven out of 12 target genes were successfully identified in clinical samples, with more than 90% coverage for most viruses. All viruses were detected by a Q30 value of more than 1%. The detection limit was measured for SARS-CoV-2, Influenza A (H1N1, H3N2), Influenza B, and human respiratory syncytial virus. The method showed 99.9% specificity in detection and was validated by 20 clinical samples. This study developed and validated a novel multiplex detection approach of Oxford Nanopore Technologies that allowed the identification of SARI-related respiratory viruses in a clinical laboratory setting.